2013
DOI: 10.1097/mpa.0b013e318259f6f0
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Role of Cannabidiol and O-1602 in Cerulein-Induced Acute Pancreatitis in Mice

Abstract: Objectives: The anti-inflammatory effects of O-1602 and cannabidiol (CBD), the ligands of G proteinYcoupled receptor 55 (GPR55), on experimental acute pancreatitis (AP) were investigated.Methods: Acute pancreatitis was induced in C57BL mice by intraperitoneal injection of 50 Kg/kg cerulein hourly, with a total of 6 times. Drugs (O-1602, 10 mg/kg, or CBD, 0.5 mg/kg) were given by intraperitoneal injection 2 times at 30 minutes before the first injection and immediately before the fifth cerulein injection. At 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
52
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 37 publications
6
52
0
Order By: Relevance
“…These studies concluded that endocannabinoids and exogenous cannabinoids may be implicated in the severity of AP, despite a dual effect (protection vs worsening) was also observed, depending of the phase of the disease. The mechanisms remain unclear and may involve sensory nerves or visceral arterial pressure, as well as pro-inflammatory processes [34][35][36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…These studies concluded that endocannabinoids and exogenous cannabinoids may be implicated in the severity of AP, despite a dual effect (protection vs worsening) was also observed, depending of the phase of the disease. The mechanisms remain unclear and may involve sensory nerves or visceral arterial pressure, as well as pro-inflammatory processes [34][35][36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…The lysate was analyzed by western blotting according to the method described[21]. The protein detection procedure adopted the enhanced chemiluminescence method (Cat No.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, CBD is under investigation in assorted clinical trials as an anti-epileptic (Devinsky et al 2014). Preclinical studies reported that CBD elicits anticonvulsant (Consroe et al 1982; Martin et al 1987), anti-inflammatory (Li et al 2013; Malfait et al 2000), and anti-tumorgenic (McAllister et al 2007) effects. Although its mechanism of action remains to be elucidated, it is known to inhibit adenosine uptake (Liou et al 2008), down-regulate the enzymes FAAH and 5-lipoxygenase (Capasso et al 2008; Massi et al 2008), and bind both transient receptor potential vanilloid 1 (TRPV1) (Iannotti et al 2014) and 5-hydroxytryptamine (serotonin) receptor 1A (5-HT1A) receptors (Russo et al 2005).…”
Section: Phytocannabinoidsmentioning
confidence: 99%